Ambiguity and Poetry: Psalm 62 as Witness - Jones, Ethan C. (2024)
Ambiguity is intrinsic and intended within biblical poetry. Psalm 62 demonstrates ways in which biblical poetry conveys this ambiguity. The form of poetry itself—its paratactic and terse shape—is the soil in which inference, reasoning, and imagination grow. There is, furthermore, an overlap between ambiguous language in general and ambiguity in poetry due to its form and intent. This essay directs modern notions of delimitation toward the realities of biblical poetry and encourages proper awareness and appreciation of ambiguity within Holy Scripture by considering its role within Psalm 62. Here the reader is challenged not only by the content of the psalm but by its form, repetition, and nuance so as to humble intellectual hubris, invite careful attention to detail, and prompt prayerful dependence on the Holy Spirit’s work of illumination and inspiration of Holy Scripture.
Keywords: Augustine; Psalm 62; Psalms; Psalter; Ambiguity; Imagination; Poetry